PERBEDAAN KARAKTERISTIK PETANI DAN USAHATANI MANGGA DI KECAMATAN PANYINGKIRAN, KABUPATEN MAJALENGKA DAN KECAMATAN JAPARA, KABUPATEN KUNINGAN - Elly Rasmikayati; Akbar Adiputra Irawan; Bobby Rachmat Saefudin; Nur Syamsiyah; Endah Djuwendah (Universitas Galuh Ciamis, 2021)
West Java Province is a productive area and has the potential for developing mango agribusiness. Majalengka and Kuningan districts are mango production centers which differ in the amount of mango production produced. The objectives of this study were: to analyzing the differences about characteristics of farmers and mango farming in Panyingkiran and Japara Districts. This research is a quantitative study using secondary data. The research method used is the method of survey results. Sampling was 130 mango farmers in Panyingkiran District and 130 mango farmers in Japara District. This research uses descriptive analysis, Independent sample T-test and Mann Whitney U-test. The results of this study indicate the characteristics of farmers and mango farming between Panyingkiran and Japara Districts have significant differences in term of the age of the farmer, the gender of the farmer, the education level of the farmer, the main job or the farmer's side job, the experience of farming mango farmers, the farmer's income from farming or other than farming. mango and mango farmer land tenure consisting of the total area of land and the number of mango trees.